2007
DOI: 10.1073/pnas.0610821104
|View full text |Cite
|
Sign up to set email alerts
|

High-field MRI of brain cortical substructure based on signal phase

Abstract: The ability to detect brain anatomy and pathophysiology with MRI is limited by the contrast-to-noise ratio (CNR), which depends on the contrast mechanism used and the spatial resolution. In this work, we show that in MRI of the human brain, large improvements in contrast to noise in high-resolution images are possible by exploiting the MRI signal phase at high magnetic field strength. Using gradient-echo MRI at 7.0 tesla and a multichannel detector, a nominal voxel size of 0.24 ؋ 0.24 ؋ 1.0 mm 3 (58 nl) was ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

45
772
4
4

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 617 publications
(825 citation statements)
references
References 57 publications
45
772
4
4
Order By: Relevance
“…Based on the visual observation on unwrapped phase images of a higher contrast between gray and white matter in AD patients than in control subjects, resulting from a higher signal intensity within the gray matter, the phase values of the cortical gray matter were determined in ROIs in four different areas of the brain-temporoparietal left, temporoparietal right, frontal, and parietal-which were positioned according a detailed human brain atlas. Because of the laminar variation in the cortical areas [29], histograms perpendicular to the cortex within these regions were created to measure peak gray matter phase values, over at least 10 cortical regions per slice and per region. To correct for local macroscopic magnetic field inhomogeneities subcortical white matter phase values were measured and used as an internal reference value.…”
Section: Image Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the visual observation on unwrapped phase images of a higher contrast between gray and white matter in AD patients than in control subjects, resulting from a higher signal intensity within the gray matter, the phase values of the cortical gray matter were determined in ROIs in four different areas of the brain-temporoparietal left, temporoparietal right, frontal, and parietal-which were positioned according a detailed human brain atlas. Because of the laminar variation in the cortical areas [29], histograms perpendicular to the cortex within these regions were created to measure peak gray matter phase values, over at least 10 cortical regions per slice and per region. To correct for local macroscopic magnetic field inhomogeneities subcortical white matter phase values were measured and used as an internal reference value.…”
Section: Image Analysismentioning
confidence: 99%
“…An alternative method to measure these susceptibility changes in the brain is to measure the relative phase in regions of interest (ROIs), because it has been shown that this is a reliable indicator of the iron content in the brain [25][26][27][28]. Although previous studies have demonstrated the potential of this approach in highfield MRI [29,30], no clinical studies have been performed yet on AD patients in vivo for the detection of AD pathology.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, MR phase imaging, acquired with a standard gradient recalled echo, has been shown to emphasize contrast between gray and white matter (Duyn et al, 2007) when compared to conventional magnitude imaging. Phase contrast was shown to be affected by tissue lipid and iron content (Duyn et al, 2007;Fukunaga et al, 2010) and the local microstructure (He and Yablonskiy, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Phase contrast was shown to be affected by tissue lipid and iron content (Duyn et al, 2007;Fukunaga et al, 2010) and the local microstructure (He and Yablonskiy, 2009). The effect of cerebral blood volume has been demonstrated to have a minor, if any, impact on the phase contrast observed between white and gray matter (Lee et al, 2010a;Marques et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of MR image phase variations may be confounded by numerous background factors such as global magnetic field inhomogeneities, nonuniform radiofrequency (RF) penetration, magnetic field gradients from air-tissue interfaces, eddy currents, etc. These artifacts lead to phase rolling and phase 2p wrapping and must be eliminated or at least minimized before true iron-related effects on phase can be assessed (27).…”
mentioning
confidence: 99%